STRATEGI PENDISTRIBUSIAN DANA SOSIAL PADA LEMBAGA SOSIAL PESANTREN TEBUIRENG (LSPT) DALAM MEMBANGUN EKONOMI MASYARAKAT DI MASA PANDEMI COVID-19 - Nafila Alfianti, Maynalia; M. Chamim; Afif, Abdullah (Irtifaq, 2022)
Abstract: This research intends to analyze the strategy of distributing social funds to the Tebuireng Pesantren Social Institution (LSPT) in building the community economy in the Covid-19 pandemic. This study used primary data sources derived from field data and secondary data obtained from appropriate literature reviews. After the data collection process will be done analysis that uses inductive, descriptive, and deductive methods. Data analysis is used to find out how the strategy of distributing social funds to Islamic financial institutions. This research uses case research and phenomenological approaches. Keywords: Social Fund. Community Economy, Covid-19 pandemic.